Epifitismo vascular em duas fisionomias vegetais, floresta paludosa e floresta estacional semidecidual no município de Botucatu, estado de São Paulo, Brasil - Marcusso, Gabriel Mendes [UNESP] (2015)
Vascular epiphytes are responsible for considerable part of tropical biodiversity. In this work was evaluated the floristic composition of vascular epiphytes, the vertical distribution and the relationship among the epiphyte community with the host tree (type of bark, height and diameter) in a swamp forest (FP) and in a seasonal semideciduous forest (FES) in the Botucatu municipality, SP. To the floristic survey were performed monthly collections during the period of one year (june 2013 to june 2014). The epiphytes were classified according with the ecological categories and the dispersion syndrome. Comparisons of the similarity among the study area with others surveys published were carried, using the Jaccard similarity index (modified). For identification were used taxonomic literature, consult to herbarium specimens and experts. The collected specimens were deposited at the Herbário Rioclarense (HRCB). To evaluate the relationship among the epiphytes and the host trees were performed linear transect along the study area, using the quadrant centered method (PAP ≥ 15 cm). Were registered 87 species of vascular epiphytes belonging to 51 genera and 13 families. The FP was the richest phytophysiognomy. Orchidaceae, Polypodiaceae, Bromeliaceae and Piperaceae were the more representative families. 72,4% were anemocoric and 87,4% obligatory holoepiphytes. 19,5 % of the species are endemic for Atlantic Domain and 33,3% from Brazil. Seven species were threatened or near threatened, two of them presumably extinct. The studied area was most similar to sites in Paraná, Rio Grande do Sul and Argentina. Of the trees, 28,2% and 56,3%, respectively in the FES and FP, showed as host tree. The tree species which had the highest number of individuals were too that which showed the highest host tree number. The host tree species Protium heptaphyllum was related to the higher scores of abundance. The holoepiphytes occured in the majority host trees in...